Governance Assesment di Provinsi Banten - Leo Agustino (Jurnal Administrasi Publik, 2005)
Governance assesment in Banten Province has been done to asses what was state, market and civil society as multi stakeholders in governing Banten Province. Governance assesment indicate ten variables, for example government effectiveness, political stability, participation, innovation and trust. Output for this assessment show that Governance Quality Index be in the last five order from 20 province, regency and city in Inodnesia. This condition be exactly the opposite of Human Development Index andP ublic Satisfaction Index that be in fourth position with score for each 66,6 and 25,1. This research shown that there is no linear correlation between Human Development Index and Public Satisfaction Index with Governance Quality Index. One factor of causes is state preference as a public service provider give score more over estimate than other actor of governance, private sector and civil society. Recommendation for the result of this research are increasing public participation in policy process, developing networking organization, public accountability enforcement and also giving incentive for government employee.Kata kunci: good governance, governance assesment, government quality index